ANALYSIS OF DRAINAGE SYSTEM MANAGEMENT IN THE NETHERLAND, FRANCE AND INDONESIA - Henny Pratiwi Adi; Slamet Imam Wahyudi (International Conference on Coastal and Delta Areas, 2015)
The drainage system is one of the most important urban infrastructure. Management quality of a city is reflected in the drainage system quality of the city. To ensure the sustainability of the drainage system, we need a system of drainage management that involves all stakeholders, including the people who reside in it. This study was conducted to determine the organization of the management of the drainage system in the Netherlands, France and Indonesia. Data collected through interviews with the parties related to the management of the drainage system in Indonesia as well as from the literature. There are three models of organization in the drainage system management which is organizations model of government-based, organization model of community-based and organization model of stakeholders-based. In general, the drainage system management in France and the Netherlands is organization model of stakeholders-based, whereas in Indonesia using organizations model of government-based and community-based. Organizations of drainage system management has a very important role, and therefore must involve competent personnel and supported by regulation and sufficient authority. Increased community participation and partnerships between government, private and community must be continued, particularly in terms of maintenance and management of the construction of drainage infrastructure and facilities that have been built.Keywords: organization model, management, drainage system